2002
DOI: 10.1073/pnas.182178199
|View full text |Cite
|
Sign up to set email alerts
|

Sleep forms memory for finger skills

Abstract: Practicing a motor skill triggers a process of memory consolidation that continues for hours after practice has ended, and becomes manifest in an improved skill at later testing. We used a sequential motor task (finger-to-thumb opposition task) to show that, in humans, the formation of motor skill memories essentially benefits from sleep. Independent of whether placed during daytime or nighttime, sleep after practice enhanced speed of sequence performance on average by 33.5% and reduced error rate by 30.1% as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

52
458
11
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 518 publications
(526 citation statements)
references
References 41 publications
(48 reference statements)
52
458
11
5
Order By: Relevance
“…8pm to 8pm) allows only 3.5-hr awake then goal-based improvements develop. Previous studies have shown that similar improvements develop provided sleep occurs within a critical time after initial practice (Fischer et al 2002;Walker et al 2003). Some procedural memories also remain susceptible to interference for a critical time following acquisition (Brashers-Krug et al 1996;Muellbacher et al 2002;Walker et al 2003).…”
Section: Discussionmentioning
confidence: 77%
“…8pm to 8pm) allows only 3.5-hr awake then goal-based improvements develop. Previous studies have shown that similar improvements develop provided sleep occurs within a critical time after initial practice (Fischer et al 2002;Walker et al 2003). Some procedural memories also remain susceptible to interference for a critical time following acquisition (Brashers-Krug et al 1996;Muellbacher et al 2002;Walker et al 2003).…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, these overnight learning gains correlated with the amount of stage two non-rapid eye movement (NREM) sleep, particularly late in the night (Walker et al, 2002). Adding to these findings, it also appears that there is no transfer of sleep-dependent procedural learning to either new motor sequences, or to performance of the same sequence using the opposite hand (Fischer et al, 2002;Korman et al, 2003), suggesting that the influence of sleep is highly specific. But while the behavioral characteristics of sleep-dependent motor learning are increasingly well characterized, the underlying neural basis of these overnight improvements remains unknown.…”
mentioning
confidence: 91%
“…wakefulness and time of day (Brawn, Fenn, Nusbaum, & Margoliash, 2010;Cajochen et al, 2004;Della-Maggiore, 2005;Doyon et al, 2009;Fischer, Hallschmid, Elsner, & Born, 2002;Keisler, Ashe, & Willingham, 2007;Kuriyama, Stickgold, & Walker, 2004;Manoach et al, 2004;Maquet, Schwartz, Passingham, & Frith, 2003 The purpose of the present study was to investigate the separate contributions of general motor skill learning and sequence-specific memory consolidation in implicit sequence learning. General motor skill learning refers to faster responses as a result of practice.…”
Section: Introductionmentioning
confidence: 99%
“…wakefulness and time of day (Brawn, Fenn, Nusbaum, & Margoliash, 2010;Cajochen et al, 2004;Della-Maggiore, 2005;Doyon et al, 2009;Fischer, Hallschmid, Elsner, & Born, 2002;Keisler, Ashe, & Willingham, 2007;Kuriyama, Stickgold, & Walker, 2004;Manoach et al, 2004;Maquet, Schwartz, Passingham, & Frith, 2003;Peigneux et al, OFFLINE CONSOLIDATION 4 2003;Spencer, Sunm, & Ivry, 2006), and degree of explicit awareness (Ghilardi et al, 2009;Hotermans, Peigneux, Maertens de Noordhout, Moonen, & Maquet, 2006;Robertson, Pascual-Leone, & Press, 2004). It is not yet clear how sequence learning per se changes from a labile state to a more stable one, although there is a large body of work on motor memory consolidation (see Krakauer & Shadmehr, 2006, for a review).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation